A shot in the dark: the use of darkness to investigate visual development and as a therapy for amblyopia. (17th June 2013) - Mitchell, Donald E
Abstract : Extended periods of complete darkness have long been used among other early experiential manipulations to explore the role of visual experience in the development of the visual pathways. In the last decade, short periods of darkness have been used to facilitate the imposition of different or conflicting visual input each day to explore the manner by which processes of perinatal development controlled by gene action are refined subsequently by visual experience. Very recently, periods of complete darkness of intermediate length (10 days) have been shown to promote very fast recovery from amblyopia induced by prior monocular deprivation (MD). When imposed immediately after a period of MD, in certain circumstances, darkness appears to insulate against the development of amblyopia. It is proposed that complete darkness may reverse maturation of many of the so‐called braking molecules in the visual cortex, so that it reverts to a more juvenile state.